Psyche at the end of life: Psychiatric symptoms are prevalent in patients admitted to a palliative care unit. Issue 3 (8th October 2015) - Masel, Eva K.; Berghoff, Anna S.; Mladen, Aleksandra; Schur, Sophie; Maehr, Bruno; Kirchhoff, Magdalena; Simanek, Ralph; Bauer, Martin; Watzke, Herbert H.; Amering, Michaela
Abstract: Objective: Our aim was to evaluate the frequency and treatment of psychiatric symptoms in patients at palliative care units (PCUs). Method: Patients admitted to one of five participating PCUs in Austria were included. The short version of the Patient Health Questionnaire (PHQ–D) was used to evaluate their mental health status. Pain intensity was rated on a numeric rating scale (NRS) from 0 to 10 by patients and physicians. Patients with a previously diagnosed psychiatric disorder were compared to those without or with newly diagnosed psychiatric symptoms, based on PHQ–D results. Pain and psychopharmacological medication were assessed. Opioid doses were converted into oral morphine equivalents (OMEs). Results: Some 68 patients were included. Previously undetected psychiatric symptoms were identified in 38% (26 of 68), preexisting psychiatric comorbidities were evident in 25% (17), and no psychiatric symptoms were observed in 37% (25). Patients with a preexisting psychiatric comorbidity received antidepressants and benzodiazepines significantly more often than patients without or with previously undetected psychiatric symptoms ( p < 0.001). Patient and physician median NRS ratings of pain intensity correlated significantly ( p = 0.001). Median NRS rating showed no significant difference between patients with preexisting, previously undetected, or without psychiatric symptoms. OMEs did not differ significantly between preexisting, without, or previously undetected psychiatric symptoms. Patients with undetected and preexisting psychiatric comorbidities had a greater impairment in their activities of daily living than patients without psychiatric symptoms ( p = 0.003). Significance of Results: Undetected psychiatric comorbidities are common in patients receiving palliative care. Screening for psychiatric symptoms should be integrated into standard palliative care to optimize treatment and reduce the psychosocial burden of the disease.